4 - The Private Provision of Higher Education in Ethiopia: Growth, Challenges, and Prospects* - Nwuke, Kasirim (Journal of Higher Education in Africa, 2008)
Since the overthrow of the Derg in 1991, the government of Ethiopia has em- barked on a number of reforms of the higher education sector. These reforms have been driven by the need to address geographical and structural imbalances in the higher education system, the increasingly sophisticated demand of both the public and expanding private sector for high quality employees, and the chang- ing context of international economic competition. The key elements of these reforms are: expanding access; addressing the geographical distribution of ac- cess; improving quality; and encouraging competition in the provision of higher education by allowing private provision. Since these reforms were enacted, the private higher education sector has grown significantly, providing both enhanced access to higher education and diversification of the higher education curricula. The emergence of a pluralistic higher education sector presents threats and op- portunities and has, as a consequence, generated considerable public policy de- bate in the country. However, there has been very little analysis of the sector to serve as a basis for decision-making. This paper seeks to provide information on the private higher education sector in Ethiopia by examining the general characteristics of the private provision sector and its contribution to expanding access and on the creation of new knowl- edge through research. It also examines the likely impact of plural providers on quality and the policy options adopted by the government. The analysis shows that the private sector is making a significant contribution to the expansion of higher education in Ethiopia, especially with respect to expanding access to women and the production of intermediate-level technical skills that the expanding Ethio- pian economy needs. Secondly, due to the relatively small size of private provid- ers and the tight regulatory restrictions on the types of courses and programmes that they offer, private higher education is unlikely to threaten the average qual- ity of higher education in Ethiopia in the short term. Concerns at this time about quality may be premature. However, due to capital and capacity constraints, the scope of the sector to contribute to the creation of new knowledge is limited. Finally, the paper argues that the future of private provision in Ethiopia depends critically on the growth of the public sector. In the short to medium term, it is the public higher education sector that will provide the bulk of the skills needed to staff the private provision sector. It will also depend on the growth of the Ethio- pian economy, on the policies of the government especially in respect of expan- sion of the public provision sector, on the behaviour, performance and conduct of public higher education institutions and on the easing of regulatory restrictions. The paper also points to the need for additional research to better understand the constraints and possibilities of the sector.